The sociology of childhood - Corsaro, William A. (Thousand Oaks, California : SAGE Publications, Inc., 2018)
William A. Corsaro's groundbreaking text,'The Sociology of Childhood', discusses children and childhood from a sociological perspective. Corsaro provides in-depth coverage of the social theories of childhood, the peer cultures and social issues of children and youth, children and childhood within the frameworks of culture and history, and social problems and the future of childhood. The'Fifth Edition' has been thoroughly updated to incorporate the latest research and the most pertinent information so readers can engage in powerful discussions on a wide array of topics. -- From publisher's description.
Part one : The sociological study of childhood. Social theories of childhood -- The structure of childhood and children's interpretive reproductions -- Studying children and childhood -- Part two: Children, childhood, and families in historical and cultural context. Historical views of childhood and children -- Social change, families, and children -- Part three. Children's cultures. Children's peer cultures and interpretive reproduction -- Sharing and control in initial peer cultures -- Conflict and differentiation in the initial peer culture -- Preadolescent peer cultures -- Part four: Children, social problems, and the future of childhood. Children, social problems, and the future of childhood -- Children, social problems, and society -- The future of childhood.
Includes glossary.
Includes bibliographical references and index.
Keywords: Children